Coordinated Control Design for Ethical Maneuvering of Autonomous Vehicles - Balázs Németh (Energies, 2023)
This paper proposes a coordinated control design method, with which the autonomous vehicle is able to perform ethical maneuvers. The starting point of the provided method is a thorough analysis on the ethical concepts for autonomous vehicle control design methods. Using the results of the analysis, an own concept is provided based on some principles of Protestant ethics. The concept focuses on improving trust in vehicle control through clear rules and predictable vehicle motion, and it is in line with the state-of-the-art ethical vehicle control methods. Moreover, an optimal Model Predictive Control (MPC) design method is formed, in which the provided ethical concept is incorporated. The outputs of the optimal control are steering angle and velocity profile, with which the ethical maneuvering can be achieved. The contribution of the paper is a coordinated control design method, which is able to involve ethical principles. Moreover, the application of Protestant ethics in this context is also a novel achievement in the paper. The effectiveness of the method through different simulation scenarios is illustrated.